The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.21037/cdt.2016.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the effect of turbulence transition on the hemodynamic parameters in human coronary arteries

Abstract: Background: Local hemodynamics plays an important role in atherogenesis and the progression of coronary atherosclerosis disease (CAD). The primary biological effect due to blood turbulence is the change in wall shear stress (WSS) on the endothelial cell membrane, while the local oscillatory nature of the blood flow affects the physiological changes in the coronary artery. In coronary arteries, the blood flow Reynolds number ranges from few tens to several hundreds and hence it is generally assumed to be lamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 36 publications
(46 reference statements)
1
31
0
1
Order By: Relevance
“…Nevertheless, critical Reynolds numbers are strongly correlated with the shape and size of the stenosis and the HR [ 13 ]. Recent research demonstrated that the fully turbulent nature of the flow occurs in cases of more than 50% stenosis [ 14 ]. However, our tests performed on the physical models demonstrated that for a 75% stenosis and low Reynolds numbers, the flow velocity profile obtained from a physical stand is the closest to the laminar model.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, critical Reynolds numbers are strongly correlated with the shape and size of the stenosis and the HR [ 13 ]. Recent research demonstrated that the fully turbulent nature of the flow occurs in cases of more than 50% stenosis [ 14 ]. However, our tests performed on the physical models demonstrated that for a 75% stenosis and low Reynolds numbers, the flow velocity profile obtained from a physical stand is the closest to the laminar model.…”
Section: Methodsmentioning
confidence: 99%
“…This model also approaches with an assumption that the blood behaves as a mixture of blood borne particulates and that mixture is considered to be continuum. The present study considers laminar blood flow through a noncompliant artery instead of turbulent flow, as a latest study by Mahalingam et al (Mahalingam et al 2016) showed that in 70% stenosis and above stenosed coronary arteries the blood flow becomes turbulent in nature, whereas, the laminar to turbulent transition of blood flow begins from 50% stenosis.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Atherosclerosis is the main underlying pathological process of CVDs, and it consists of an inflammatory disorder induced by several unhealthy behaviors and lifestyles, that causes the narrowing of the arteries' lumen [1]. During early stages, there are no significant changes in the flow dynamics, nevertheless, as time progresses, these plaques play a critical role in altering the flow characteristics and transition to turbulence can occur, even at much lower Reynolds number [2], [3]. To understand the flow field changes, several hemodynamic studies have been conducted [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, computational models have been used as an auxiliary tool for obtaining more reliable results [7]- [9]. In particular, fluidstructure interaction (FSI) [10] and computational fluid dynamics (CFD) [4] have been used as an effective alternative to investigate in detail several blood flow phenomena in blood vessels and an important component in the study of CVDs, allowing the calculation of various hemodynamic parameters with high precision [2], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation